THE ROLE OF SMART FITNESS DEVICES WITH AI IN OBESITY PREVENTION AND HEALTH MONITORING - Radojčić, Vesna; Dobrojević, Milos (ACADEMIC REVIEW, 2025)
Modern lifestyle, the abundance of high-calorie food, and the lack of physical activity have led to a global increase in obesity rates. In this context, the development of smart fitness equipment powered by artificial intelligence (AI) represents significant potential for enhancing physical activity, monitoring health parameters, and providing personalized guidance for weight loss and fitness improvement. This paper explores the functionalities and advantages of AI-equipped fitness devices, including physiological parameter monitoring, motion analysis through computer vision, detection of improper exercise execution, and automated adjustment of training plans. Special attention is given to the role of these technologies in obesity prevention among adults, as well as their potential for early detection of health risks. In addition to the literature review, the paper incorporates a practical case study conducted in Bijeljina, Bosnia and Herzegovina, where AI-integrated smart fitness equipment is already in use. This example illustrates the real-world implementation of such technologies and highlights their relevance for improving public health outcomes. Through a combined methodological approach, the paper examines actual and practical examples of successful applications of AI-powered fitness systems and discusses the challenges of their broader implementation within the context of public health.